Fe3+/H2O2 Fenton degradation of wastewater containing dye under UV irradiation. Issue 38 (14th August 2016) - Xu, Hang; Yu, Tianlong; Guo, Xiaoxi; Wang, Jianxu
Abstract: We analyzed the photocatalytic effect of ultraviolet on Fe 3+ /H2 O2 Fenton degradation of simulated printing sewage containing Reactive Red 6B. Online spectrometry was picked for monitoring to provide more accurate data which is invariably erred by complicated alkali termination in more conventional methods. The photocatalytic effect of ultraviolet on the Fe 3+ /H2 O2 Fenton process was assessed by the coefficients of UV promoting effect and reagent utilization under different conditions (Fe 3+ concentration, H2 O2 concentration, and pH value). Removal efficiency reached 100% at the optimal condition: 50 × 10 −5 mol/L Fe 3+, 1 × 10 −2 mol/L H2 O2, and pH 4. Finally, a possible degradation pathway of Reactive Red 6B was proposed.